Further Evidence That Defects in Main Thyroid Dysgenesis-Related Genes Are an Uncommon Etiology for Primary Congenital Hypothyroidism in Mexican Patients: Report of Rare Variants in FOXE1, NKX2-5 and TSHR - Miguel Angel Alcántara-Ortigoza; Iraís Sánchez-Verdiguel; Liliana Fernández-Hernández; Sergio Enríquez-Flores; Aidy González-Núñez; Nancy Leticia Hernández-Martínez; Carmen Sánchez; Ariadna González-del Angel (MDPI AG, 2021)
Mexico shows a high birth prevalence of congenital hypothyroidism (CH) due to thyroid dysgenesis (TD). PAX8 defects underlie only 1% of these cases and NKX2-1 does not seem to be involved. Here, we analyzed other TD-related genes in 128 non-related Mexican patients (females 77.3%; 6 months to 16.6 years) with non-syndromic CH-TD diagnosis established by clinical evaluation, thyroid hormone serum profiling, and scintigraphy (74%) or ultrasonography (26%). We performed Sanger sequencing of FOXE1, NKX2-5, and TSHR and evaluated copy number variations (CNVs) in TSHR, FOXE1, PAX8, and NKX2-1 by multiplex ligation-dependent probe amplification. Odds ratios for TD risk were explored for FOXE1 polyalanine stretches [polyAla-rs71369530] in cases and controls (N = 116). Five rare missense changes cataloged as benign (NKX2-5:p.(Ala119Ser)-rs137852684), of unknown significance (FOXE1:p.(Ala335Gly)-rs543372757; TSHR:p.(Asp118Asn)-rs1414102266), and likely pathogenic (FOXE1:p.(Gly124Arg)-rs774035532; TSHR:p.(Trp422Arg)-rs746029360) accounted for 1.5% (N = 2/128) of clinically relevant genotypes (supported in part by protein modeling) in CH-TD. No CNVs were identified, nor did polyAla > 14 alanines in FOXE1 significantly protect against TD. The present and previously published data collectively show that small clinically relevant germline variants in PAX8, FOXE1, and TSHR are found in only a very small proportion (2.5%) of isolated CH-TD Mexican patients.